2010
DOI: 10.1121/1.3409478
|View full text |Cite
|
Sign up to set email alerts
|

Echolocation signals of a beaked whale at Palmyra Atoll

Abstract: Acoustic recordings from Palmyra Atoll, northern Line Islands, central Pacific, showed upsweep frequency modulated pulses reminiscent of those produced by beaked whales. These signals had higher frequencies, broader bandwidths, longer pulse durations and shorter inter-pulse intervals than previously described pulses of Blainville's, Cuvier's and Gervais' beaked whales [Zimmer et al. (2005). J. Acoust. Soc. Am. 117, 3919-3927; Johnson et al. (2006). J. Exp. Biol. 209, 5038-5050; Gillespie et al. (2009). J. Acou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 45 publications
1
44
0
1
Order By: Relevance
“…The ICI was consistent throughout the burst pulse, unlike the decreasing ICI found in terminal buzzes in Blainville's beaked whales and the Palmyra beaked whale (Johnson et al, 2006;Baumann-Pickering et al, 2010). These burst pulses had energy in frequency ranges similar to that found in Blainville's beaked whale (Rankin and Barlow, 2007) and Baird's beaked whale (Dawson et al, 1998).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The ICI was consistent throughout the burst pulse, unlike the decreasing ICI found in terminal buzzes in Blainville's beaked whales and the Palmyra beaked whale (Johnson et al, 2006;Baumann-Pickering et al, 2010). These burst pulses had energy in frequency ranges similar to that found in Blainville's beaked whale (Rankin and Barlow, 2007) and Baird's beaked whale (Dawson et al, 1998).…”
Section: Discussionmentioning
confidence: 51%
“…Although the frequency structure of click and pulse sounds for Longman's beaked whale overlap with those of other species of beaked whale (e.g., Baird's beaked whale, northern bottlenose whale); they are distinct from the known signals for species with an overlapping distribution in their spectral properties [specifically, Blainville's beaked whales and Cuvier's beaked whale (Ziphius cavirostris)]. Likewise, the FM pulses presented here are spectrally and temporally distinct from the FM pulses attributed to beaked whale sounds at Palmyra Atoll (Baumann-Pickering et al, 2010) andCross Seamount (McDonald et al, 2009). The short 15 and 25 kHz click sounds overlap in peak frequency with click sounds produced by delphinids in the region, such as false killer whales and short-finned pilot whales (S. Baumann-Pickering, personal communication) and may not be useful for species identification.…”
Section: Discussionmentioning
confidence: 56%
“…Visually confirmed towed array recordings of M. europaeus, a species also present in Bahamian waters, and Hyperoodon ampulatus have been reported to have similar characteristics to M. densirostris and Z. cavirostris clicks (Gillespie et al, 2009;Wahlberg et al, 2011) but with slightly different center frequencies. Autonomous recorders have recorded beaked whale-like sounds in a variety of areas (Baumann-Pickering et al, 2010) over long durations, although it has proven challenging to allocate these sounds to species in the absence of visual confirmation.…”
Section: Introductionmentioning
confidence: 99%
“…3) found that detection probability of a single click drops to 0.4-0.6 at zero horizontal distance. Beaked whales produce approximately 2-10 clicks per second (Baumann-Pickering et al, 2010) and frequently change their orientation to scan for potential prey items . Consequently, if the probability of detecting a single click is high at zero horizontal distance, then we feel confident that the probability of detecting a group of beaked whales over a finite time period (say, 1 min) must be near certainty given that each individual is making multiple clicks every second.…”
Section: Estimation Of Detection Probabilitymentioning
confidence: 99%
“…Recent work has characterized echolocation signals of several beaked whale species and has shown that these signals are species-specific (Dawson et al, 1998;Hooker and Whitehead, 2002;Johnson et al, 2004;Madsen et al, 2005;Zimmer et al, 2005;Johnson et al, 2006Johnson et al, , 2008Gillespie et al, 2009;Baumann-Pickering et al, 2010). Behavioral studies using acoustic recording tags attached to beaked whales with suction cups have revealed that two beaked whale species (Cuvier's beaked whale-Ziphius cavirostris and Blainville's beaked whale-Mesoplodon densirostris) produce echolocation clicks almost continuously when foraging and seldom echolocate or produce communication sounds when they are not foraging , Aguilar de Soto et al, 2012.…”
Section: Introductionmentioning
confidence: 99%